Validation of the name Persea himalayensis (Lauraceae) - Kumar, Venkatachalam Sampath; Gangopadhyay, Mohan (Phytotaxa, 2013)
In the publication of the new species “Persea himalayaensis”, Gangopadhyay (2006) did not cite a nomenclatural type and thus the species name was not validly published. In an attempt to correct the situation, we (Gangopadhyay & Kumar 2009) referred to the 2006 publication and republished “Persea himalayaensis”. At that time, it was assumed that for validation of such names lectotypification was necessary. Accordingly, we designated “Wall. Num. List no. 2607B” (CAL) as the “lectotype”. We did not realize that our validation attempt amounted to publishing the name of a new species and that a holotype citation was essential (Vienna Code Art. 37.6 ICBN, McNeill et al. 2006).